Detection of multidrug-resistance Staphylococcus aureus from mastitic cows’ milk in Dakahlia and Damietta Governorates, Egypt - Gabr, Alaa; Sadat, Asmaa; Younis, Gamal (Journal of Advanced Veterinary Research, 2024)
Staphylococcus aureus (S. aureus) is an important microbe which has the ability to cause a mastitis in cows and causes huge economic losses. This microorganism has a growing ability to resist antimicrobial agents which let to hinder the treatments programs. The study aimed to isolate and identify the prevalence of multi-drug resistant S. aureus in mastitic cows’ milk in delta region (Dakahlia and Damietta governorates). A two hundred milk samples were randomly selected from clinical mastitic and sub-clinical mastitic infected cows (one hundred from each); these infected cows farms located at Dakahlia and Damietta governorates during the period of November 2020 to March 2021. The samples were diagnosed using routine culture methods to isolate S. aureus. All suspected colonies were subjected to biochemical analysis for the basic identification of S. aureus colonies. The biochemically identified S. aureus colonies were confirmed by using molecular marker targeting thermonuclease-nuc gene by PCR. All the confirmed S. aureus isolates were subjected to antimicrobial sensitivity testing against eighteen antimicrobial agents by using Kirby–Bauer disc diffusion method. Out of the 200 tested milk sample, a forty-six were identified as S. aureus isolate revealed a total prevalence 23%. S. aureus prevalence rate in clinical mastitic and sub-clinical mastitic samples was 37 (80.4%), and 9 (19.6%), respectively. S. aureus isolates revealed a high resistant against oxacillin, ampicillin, and ceftiofur, and moderate resistance against tetracycline, amoxicillin- clavulanic acid, cefotaxime, cefuroxime, vancomycin, and gentamycin, while a high sensitivity of S. aureus was displayed against ciprofloxacin, SXT and marbofloxacin. All examined S. aureus isolates were sensitive against imipenem. Multidrug resistance (MDR) was displayed in all the isolates. Building food tracking and farm animal surveillance systems is essential to improving the healthiness processing and guaranteeing that consumers receive safe food.